Surgical Treatment of Left Ventricular Pseudoaneurysm - Mujanovic, Emir (Med Arch, 2014)
INTRODUCTION: Left ventricular pseudoaneurysm is a rare condition because in most instances ventricular free-wall rupture leads to fatal pericardial tamponade. Rupture of the free wall of the left ventricle is a catastrophic complication of myocardial infarction, occurring in approximately 4% of patients with infarcts, resulting in immediate collapse of the patient and electromechanical dissociation. In rare cases the rupture is contained by pericardial and fibrous tissue, and the result is a pseudoaneurysm. The left ventricular pseudoaneurysm contains only pericardial and fibrous elements in its wall-no myocardial tissue. Because such aneurysms have a strong tendency to rupture, this disorder may lead to death if it is left surgically untreated. CASE REPORT: In this case report, we present a patient who underwent successful repair of a left ventricular pseudoaneurysm, which followed a myocardial infarction that was caused by occlusion of the left circumflex coronary artery. Although repair of left ventricular pseudoaneurysm is still a surgical challenge, it can be performed with acceptable results in most patients.